Pengaruh Cordyceps militaris terhadap mortalitas rayap (Coptotermes curvignathus Holmgren) (Isoptera: Rhinotermitidae) di laboratorium - Arkhiadi Benauli Tarigan; Maryani Cyccu Tobing; Syahrial Oemry (Universitas Sumatera Utara, 2015)
The influence of Cordyceps militaris on Coptotermes curvignathus Holmgren. (Isoptera: Rhinotermitidae) mortality in laboratory. This research was to study influence of entomophatogen fungus C. militaris against C. curvignathus in laboratory. This study was conducted in Pest Laboratory of Agriculture Faculty, University of Sumatera Utara, Medan during of October 2014 with using completely randomized design (CRD) nonfactorial with nine treatments and three replications : control, C. militaris sprayed (10, 20, 30 and 40 g/ 100 ml water), C. militaris sowed (10, 20, 30 and 40 g). The results showed that the highest mortality (100%) of C. militaris on sprayed 30 and 40 g/ 100 ml water and sowed 30 and 40 g in seventh day; the lowest (78.33%) on C. militaris sprayed 10 g/ 100 ml water. Termites was infected by C. militaris suffered mimification and after a few days the colonies was growth with white colored (micelium) around the body. The fastest of mortality time at 50% was 3.67 days on C. militaris sowed 40 g and the longest was 5.00 days on C. militaris sprayed 10 g/ 100 ml water and C. militaris sowed 10 g.Keywords : Coptotermes curvignathus, Cordyceps militaris, mortality, spray, sowe